2019
DOI: 10.1002/wfs2.1341
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles used for fingermark detection—A comprehensive review

Abstract: Nanoparticles (NPs) have been used in numerous fields such as medicine, imaging, and electronics to cite just a few. In forensic science, NPs have been researched specifically for the detection of fingermarks. Their small size, surface functionalization ability, and luminescence properties can potentially lead to better resolution, increased sensitivity, and selectivity. This paper offers an extensive review of the various NP types investigated over the past three decades. NPs are sorted into seven categories,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 227 publications
(371 reference statements)
0
31
0
Order By: Relevance
“…[3] The latter appears to be the best option for personal identification due to their uniqueness and complexity of ridge patterns. [4] Despite the fact that nanoparticles are found to be a potential tool for LF detection, [5] development of novel systems is still required in order to finally take them into routine use. Thus, validation of nanoparticles should fulfill three desirable properties at the same time: i) particles with nanometric range (up to 100 nm), ii) to be facilely functionalized onto the surface (to permit the selective targeting of fingermark components) and, iii) to have optical properties that facilitate fingermark visualization post development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] The latter appears to be the best option for personal identification due to their uniqueness and complexity of ridge patterns. [4] Despite the fact that nanoparticles are found to be a potential tool for LF detection, [5] development of novel systems is still required in order to finally take them into routine use. Thus, validation of nanoparticles should fulfill three desirable properties at the same time: i) particles with nanometric range (up to 100 nm), ii) to be facilely functionalized onto the surface (to permit the selective targeting of fingermark components) and, iii) to have optical properties that facilitate fingermark visualization post development.…”
Section: Introductionmentioning
confidence: 99%
“…[11] In theory, the use of nanoparticles could result in greater ridge pattern clarity than using the micron-sized particles in traditional powders that normally contain particles in the submicron to micrometer range. [12] The ability to deposit a greater number of luminescent nanoparticles along a ridge may also provide enhanced contrast between the ridge and substrate [5]. From a mechanistic point of view, recent studies have shown that hydrophobicity is a major yardstick to fingerprinting development mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we demonstrate the synthesis and functionalization of non-10 B enriched polymer-coated quasi-spherical boron carbon oxynitride (BCNO) nanoparticles as an effective boron drug for BNCT (Scheme 1). BCNO is a non-toxic, non-rare earth and earthfriendly phosphor with application in light emitting diodes (LEDs) [52][53][54][55][56], highly sensitive fingerprint readers [57,58], toxic metal sensors [57,59,60], and in high contrast cellular imaging [61,62]. In contrast to previously reported boron nanomaterials, BCNO possesses an inherent photoluminescence (PL) property without the need of an additional labelling chemistry for imaging purposes.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods mostly develop the fingermarks that luminesce within the visible part of the spectrum and there are many potentially interfering substrates that also luminesce within this region, which could result in lack of contrast and low sensitivity of these techniques. Nanotechnology in combination with luminescence is a particularly promising approach to embrace the challenges of latent fingermark detection (Dilag et al, 2011;Kanodarwala et al, 2019;Menzel, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In specific relation to this review, the optical properties of some nanoparticles can be employed to enhance the visibility of developed latent fingermarks by tuning the photoluminescence characteristics of the luminescent nanoparticle to regions of the spectrum where there is minimal luminescence from the background materials. These can be tailored through their composition, size, morphology, or surface modification to achieve the desired photoluminescence specifications (Dilag et al, 2011;Kanodarwala et al, 2019;Le sniewski, 2016;Stoilovic & Lennard, 2012). Some nanoparticles are inherently luminescent such as quantum dots (QDs), lanthanide-doped nanoparticles, polymer nanoparticles, and zinc oxide nanoparticles, while others can be associated with luminescent agents such as silica nanoparticles or metal oxide nanoparticles encapsulated luminescent dyes.…”
Section: Introductionmentioning
confidence: 99%